Conceptual principles of knowledge management in integrated systems for the implementation of construction projects - CHUPRYNA , Iurii (Ways to Improve Construction Efficiency, 2025)
Knowledge management is viewed as a strategic factor in ensuring the efficiency and innovativeness of construction projects in the modern dynamic environment. The information and cognitive potential of project teams becomes a key resource that determines the competitiveness, resilience, and adaptability of organizations. Unlike material resources, knowledge possesses a nonlinear nature – it is continuously renewed, enriched through participants’ interaction, and transformed as a result of the digitalization of management processes. The article substantiates the concept of an integrated approach to knowledge management, which ensures a continuous cycle of knowledge creation, accumulation, transfer, utilization, and renewal throughout the life cycle of a construction project. Knowledge is interpreted as a dynamic system of interaction among experience, information, and analytics. The role of digital platforms, BIM technologies, and cloud-based knowledge repositories is emphasized as essential tools for integrating knowledge flows among project participants. The effectiveness of knowledge management is based on the coherence of information flows and the bidirectional communication between architects, engineers, contractors, and clients. A methodological approach to quantitative measurement of knowledge efficiency is developed through specific indices – the Knowledge Utilization Efficiency Coefficient and the Integration Interaction Index. These indicators reflect the level of information exchange, response speed, reuse of solutions, and the degree of digital integration. The proposed models of the synergistic effect of knowledge management and the diffusion of knowledge over time demonstrate how collective learning enhances team performance and reduces decision-making time. The practical significance of the study lies in the creation of a conceptual model of knowledge management that combines horizontal (intra-team) and vertical (managerial) information flows. This combination forms an integrated informational environment where knowledge acquires self-replicating properties, and collective competence grows geometrically. The proposed system establishes a foundation for the development of an intellectual management culture that ensures sustainability, flexibility, and effectiveness of construction organizations in the context of the industry’s digital transformation.